HADIS LARANGAN MEMINTA JABATAN: ANALISIS KUALITAS DAN RELEVANSINYA DENGAN PEMIKIRAN IBNU TAIMIYAH - Yulia Pratami Putri; Oldha Fauzia (STKIP Subang, 2026)
This research investigates the authenticity of the hadith concerning the prohibition of seeking a position of leadership and its relevance to Ibn Taymiyyah’s thought. In the context of religious life, Islam as a teaching that regulates all aspects of life, including governance, provides ethical and moral guidelines for individuals involved in the bureaucratic world. In this context, the act of seeking certain positions has a significant impact on the effectiveness and sustainability of governance. This research uses a qualitative method with a type of library research. This study concludes the status of the hadith about the prohibition of seeking positions narrated by At-Tirmidhi in the Sunan At-Tirmidhi book number 7146 in terms of its transmission; this hadith is classified as Marfu’ because it originates from the transmission of the Prophet Muhammad (SAW). Then, if viewed from the criteria of the authenticity of a hadith, this hadith meets the five criteria of authenticity. Therefore, the hadith narrated by At-Tirmidhi is considered authentic and can be used as evidence. In relation to Ibn Taymiyyah's thoughts, seeking positions is prohibited. According to Ibn Taymiyyah, a leader must be chosen based on competence, honesty, and integrity, not because of personal or political relationships. However, the appointment of ministers in Indonesia today often does not consider these competencies. Many ministerial positions are filled by individuals with political backgrounds rather than those with competence in the relevant fields.